Segregated input to thalamic areas that project differently to core and shell auditory cortical fields - Tetsufumi Ito; Mamiko Yamamoto; Li Liu; Khaleeq Ahmad Saqib; Takafumi Furuyama; Munenori Ono (iScience)
Summary: Perception of the environment is multimodal in nature, with sensory systems intricately interconnected. The ability to integrate multimodal sensations while preserving the distinct characteristics of each sensory modality is crucial, and the underlying mechanisms of the organization that facilitate this process require further elucidation. In the auditory system, although the concept of core and shell pathways is well established, the brain-wide input/output relationships of thalamic regions projecting to auditory-responsive cortical areas remain insufficiently studied, particularly in relation to non-auditory structures. In this study, we utilized functional imaging and viral tracing techniques to map the brain-wide connections of core and shell pathways. We identified three distinct shell pathways, in addition to a core pathway, each exhibiting unique associations with non-auditory structures involved in behavior, emotion, and other functions. This architecture suggests that these pathways contribute differentially to various aspects of multimodal sensory integration.